UNIVERSITY STUDENTS' OPINION ON THEIR INSTRUCTIONAL MOTIVATION - Carmen Maria ȚÎRU; Maria LUNGU (Universitaria Publishing House, Craiova, 2023)
Instructional motivation is relevant for student academic success and the improvement of teaching strategies. Many factors contribute to the growth of student's motivation to learn. The scientific literature investigated this issue and its different dimensions related to specific components of the educational process at the university level. This study investigates the opinion of university students on their level of instructional motivation, after a semester of using the ARCS model in the teaching process. The students' responses showed a percentage over 50% for instructional motivation with high frequencies of manifestation in the specific dimension of ARCS model. Knowing the opinion of the students about their instructional motivation, teachers could use it in the teaching process and improve their teaching strategies. Also, by adapting the teaching model to students' instructional motivation, the results could be an educational context supporting students who are not so well motivated for the instructional learning process.